109k views
0 votes
What of the following us a solution to the system of equations​

What of the following us a solution to the system of equations​-example-1

1 Answer

1 vote

Answer:

(- 1, - 5 )

Explanation:

Given the 2 equations

y = 3x - 2 → (1)

6 + y = - x → (2)

Substitute y = 3x - 2 into (2)

6 + 3x - 2 = - x

4 + 3x = - x ( add x to both sides )

4 + 4x = 0 ( subtract 4 from both sides )

4x = - 4 ( divide both sides by 4 )

x = - 1

Substitute x = - 1 into (1) for corresponding value of y

y = 3(- 1) - 2 = - 3 - 2 = - 5

solution is (- 1, - 5 )

User Maksim Simkin
by
6.2k points